Community based monitoring under national rural health mission in Maharashtra: Status at primary health centers - Prakash Prabhakarrao Doke; Ashok Purshottamrao Kulkarni; Pushpa Omprakash Lokare; Muralidhar Tambe; Ratnendra R Shinde; Mohan B Khamgaonkar (Wolters Kluwer Medknow Publications, 2014)
This study compares the implementation of community-based monitoring (CBM) in 45 primary health centers (PHCs) in the pilot phase in Maharashtra with the equal number of randomly selected PHCs not implementing CBM (non-CBM) from the same districts. Information was collected by teams from Community Medicine Departments by visiting selected PHCs. Establishment of monitoring committees and training of medical officers (MOs) had been completed as required but only 36.36% MOs were trained. Only 43.18% MOs received the facility report card. Most of the MOs (90.90%) attended Jansunwai and opined that it had increased community awareness and the barriers between the people and PHC staff were broken. There was no difference in fund utilization and meetings of Rugna Kalyan Samittees. Percentage of Institutional deliveries and women receiving Janani Suraksha Yojana benefits among home deliveries was more in the non-CBM group of PHCs.